Implementation of Policies with No Cigarette in Inpatient Health Center Way Kandis Bandar Lampung - Laura Panggabean, Edith; Rafeni RACHMAWATIb (RADINKA JAYA UTAMA PUBLISHER, 2024)
The application of a smoking area is an effort to protect the public against the risk of threats of health problems because the environment is contaminated with cigarette smoke. The application of this no-smoking area needs to be held in healthcare facilities such as health centers. One health center in the city of Bandar Lampung that has implemented KTR within the Puskesmas is the Way Kandis inpatient Puskesmas Bandar Lampung. This type of research is descriptive with qualitative methods. The research data was obtained from the results of interviews, observation, and documentation. Data analysis uses interactive data analysis from Miles and Huberman. The results of the study show that the implementation of the No Smoking Area Policy at the Way kandis Health Center has not been fully implemented. Submission of the policy of no-smoking areas in the Puskesmas inpatient Way Kandis is not yet maximum there are still visitors who violate the rules of KTR, and there is no special team to support and control smoking activities in the Puskesmas inpatient Way Kandis. The study concludes that the implementation of the No Smoking Area Policy cannot work well if there are several aspects of inhibition, namely communication, resources, disposition, and bureaucratic structure. Suggestions are the need for resources including human resources, budget, and facilities. Can provide socialization media through periodic promotional videos and health information about Non-Smoking Areas and strict enforcement of sanctions.